MANUSIA SEBAGAI KHALIFAH DALAM PERSFEKTIF ISLAM - Rahmat Ilyas (MAWA IZH JURNAL DAKWAH DAN PENGEMBANGAN SOSIAL KEMANUSIAAN, 2016)
Human existence as a creature of God's creation on this earth has an important role in its function as a vicegerent on earth. Allah not only regulates the life associated with the worship of God, but God also regulate how humans perform its role on this earth as caliph who aims to be the safety of the world and the hereafter. In the Islamic concept, man is the vicegerent namely as a representative, a replacement or a god in advance bumi.dengan ambassador of his position as Caliph of Allah on earth, man will be held accountable before him. About how he was a holy duty caliphate. Therefore, in executing the responsibilities that humans are equipped with a variety of potential as a mind that provides the ability for humans to do so